Future ocean biomass losses may widen socioeconomic equity gaps - Daniel G. Boyce (Nature Portfolio, 2020)
Numerous marine ecosystem models are used to project animal biomass over time but integrating them can be challenging. Here the authors develop a test for statistical significance in multi-model ensemble trends, and thus relate future biomass trends to current patterns of ecological and socioeconomic status.